2008
DOI: 10.3802/jgo.2008.19.3.157
|View full text |Cite
|
Sign up to set email alerts
|

Present status and future direction of clinical trials in advanced endometrial carcinoma

Abstract: Endometrial adenocarcinoma is staged surgically, and advanced endometrial carcinoma is considered to be FIGO stage III and IV. The Gynecologic Oncology Group (GOG) has come a long way in developing new strategies in the management of advanced endometrial carcinoma. Combining surgery, radiation, and chemotherapy, the 5-year survival has improved to between 40-60% in newly diagnosed advanced endometrial carcinoma. Recent findings in GOG184 indicate that multiple risk factors noted at the time of surgical staging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…However, the therapeutic value of chemotherapy and radiation therapy in the treatment of ovarian steroid cell tumor, NOS, is poorly understood due to the rarity of this tumor and the early stage of diseases in the majority of cases [20]. There are some studies that showed efficacy of combination chemotherapy (bleomycin, etoposide, and cisplatin) for stage II primary malignant ovarian stromal tumors, metastatic, and recurrent diseases [21,22].…”
Section: Discussionmentioning
confidence: 98%
“…However, the therapeutic value of chemotherapy and radiation therapy in the treatment of ovarian steroid cell tumor, NOS, is poorly understood due to the rarity of this tumor and the early stage of diseases in the majority of cases [20]. There are some studies that showed efficacy of combination chemotherapy (bleomycin, etoposide, and cisplatin) for stage II primary malignant ovarian stromal tumors, metastatic, and recurrent diseases [21,22].…”
Section: Discussionmentioning
confidence: 98%
“…BLOOD, 11 APRIL 2013 x VOLUME 121, NUMBER 15 tAML RISK AFTER CHEMOTHERAPY IN ADULTS, 1975-20082997 For personal use only. on May 11, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…We report newly emerging tAML risks coincident with the expanding use of chemotherapy for cancers of the esophagus, anus, cervix, endometrium, and prostate, which have been suggested previously in case reports. [36][37][38] For esophageal, anal, cervical, and endometrial cancers, the emerging tAML risks could be related to the addition of platinumbased regimens to standard treatment approaches for certain patients, [39][40][41] whereas for prostate cancer, risks may be associated with an increasing role of chemotherapy in the (neo)adjuvant setting and for the treatment of castration-resistant disease. 42 We also observed an increased risk for tAML after bone and joint cancers since the 1990s, which may be associated with the addition of ifosfamide and etoposide to standard chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The non endometrioid group that includes serous (SC) and clear cell (CC) endometrial cancer accounts for 10%-15% of all endometrial cancer cases, but the mortality from this cancer accounts for 50% of overall endometrial cancer mortality. When relapse occurs, response to systemic therapy is limited and survival is low [4].…”
Section: Introductionmentioning
confidence: 99%